Electromechanical Modelling of a Piezoelectric Stack Energy Harvester - Matthew Evans; Lihua Tang; Chris Bowen; Aiguo P. Hu; Kai Tao; Kean Aw (Proceedings, 2018)
In this paper, the behavior of a piezoelectric stack generator subject to a direct mechanical force, such as that experienced by pedestrian loads, is characterized and modelled. A lumped element model is developed that describes the electrical output of piezoelectric stack generators for quasi-static, off-resonance and random input conditions which are typical of underfloor or supporting structure energy harvesters. This research demonstrates the ability for accurate predictions of output voltage and current based on the material properties and geometry of the piezoelectric stack. The behavior of real-world random loading patterns is incorporated in the model, pairing mechanical input with interfacing circuitry requirements in order to maximize energy transfer. The developed model facilitates time-efficient design by reducing the simulation time to the order of seconds.